Characterization And Hydrocarbon Potentiality Of The Nubia Reservoir In The October Field, Central Gulf Of Suez, Egypt / t - Mostafa Abdalla Taha Abdalla Khattab; Mohamed Ibrahim El-Anbaawy; Adel Abdel Moneim El-Tehiwy; Mohamed Hassan Mansour (2024)
The main purposes of this work are to analyze the main reservoir characteristics of the Nubia sandstone clastics and evaluate the results to outline a development plan for the area of interest. Update the structural and depositional facies models as well as subdividing the main zones of the Nubia sandstone into smaller subzones to support the dynamic operations for measuring the cumulative oil production.
(3JNJU gPg GdQSGdI HJbjje NRGf GdMLQ GdQedj GdfhHj aj Mbd CcJhHQ HNdjL GdShjS hPdc HJMOjK JbSje UNhQ GdNRGf Gdj YOI fWGbGJ JaUjdjI(B. (3hHfGA fehPL JQcjHj LOjO djchf CSGSG dHfGA fehPL LOjO dJJGHY hJWhQ GdSMfGJ GdJQSjHjI hPdc HGSJYeGd WQb GdfePLI GdeLSeI hHQGeL GdMGSH GdGdj GdeJbOeI aj JaSjQ fJGFL GdBHGQ hGdNUGFU GdHJQhajRjGFjI hOeLgG eY GdeSM GdSjRej GdeLSe YGdj GdObI HZQV JWhjQ GdBHGQ GdMGdjI hRjGOI GfJGLgG hLhOJg hGbJQGM ehGbY dBHGQ LOjOI JSGYO aj JfejI Mbd CcJhHQs
Thesis (M.Sc.)-Cairo University, 2024.
Bibliography: pages 112-122.
Issued also as CD
Text in English and abstract in Arabic & English.
Keywords: Geology; Reservoir characteristics -- Nubia sandstone clastics -- development plan